The Effect of Using Teaching with Motor Tasks According to Total and Partial Training in Developing Attention Focus and Learning Some Types of Shooting in Basketball - Emad Toma Radi (Journal of Global Pharma Technology, 2018)
Variability and overlap in teaching and learning methods achieve high percentages of development in characteristics, skills and other aspects of teaching strategies and methods. Teaching is one of these methods using motor tasks which currently play an effective role in modern teaching through which a part of the teacher’s authorities is transferred to students.  The problem of the study lies in that teachers did not use modern teaching methods, training schedule and organization and they kept the concept of generality in teaching and learning these skills. They also did not consider effective factors and conditions, so the researcher conducted this study to solve this problem. However, the researchers used the empirical method. The sample was represented in students of the first grade at the Sport Education Department in the college of Basic Education, AL-Mustansiriyah University (40 students). The sample was  divided into a first experimental group (20 students) using the method of teaching with motor tasks due to total training and second experimental group (20 students) using the method of teaching with motor tasks due to partial training. The researchers conducted sample homogeneity, applied tests of attention focus and skill tests. Pre-tests were applied on the sample of the study with the use of teaching method of motor tasks in the class units. Researchers concluded that:There are differences between pre and post tests for both experimental groups which refer that teaching using motor tasks due to pre and post training was more affective. Results showed that the second experimental group excelled in attention focus using teaching with motor tasks due to partial training. Results showed that the second experimental group excelled in learning some types of scoring from the free throw line and peaceful scoring using teaching with motor tasksKeywords: Effect teaching, Motor Learning & Basketball skills.